2019
DOI: 10.2139/ssrn.3480718
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and Sectoral Allocation: The Labor Market of School Principals

Abstract: An important question is whether differences in management can explain variation in productivity and whether different compensation schemes and selection policies can impact the allocation of managerial effectiveness. To investigate this, we measure the value-added of school principals and study their labor market outcomes in Chile, where a large subsidized private sector competes with public sector schools. Using large administrative data sets on student performance and school personnel, we document substanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 132 publications
(117 reference statements)
0
1
0
Order By: Relevance
“…The combination of independent measures of teaching practices and panel data on student learning allow us to present direct evidence on the correlation between school management quality and independent measures of school effectiveness and productivity. 7 Third, we complement the literature on school leadership where multiple papers have studied the impact of changes in principals and superintendents on school quality, and shown that school leaders "matter" (Coelli and Green;Walsh and Dotter;2020;Lavy and Boiko;2017;Munoz and Prem;2020). Yet, for the most part, this literature has not consistently measured specific practices of school leaders.…”
Section: Introductionmentioning
confidence: 96%
“…The combination of independent measures of teaching practices and panel data on student learning allow us to present direct evidence on the correlation between school management quality and independent measures of school effectiveness and productivity. 7 Third, we complement the literature on school leadership where multiple papers have studied the impact of changes in principals and superintendents on school quality, and shown that school leaders "matter" (Coelli and Green;Walsh and Dotter;2020;Lavy and Boiko;2017;Munoz and Prem;2020). Yet, for the most part, this literature has not consistently measured specific practices of school leaders.…”
Section: Introductionmentioning
confidence: 96%